Determinação voltamétrica de tiofenos, sulfetos, sulfóxidos e sulfonas em matrizes asfálticas empregando eletrodo de mercúrio - Silva, Chrys Katielli Hoinacki da (2016)
Sulfur compounds in petroleum asphalt cement (CAP) are related to quality parameters such as reactivity, corrosivity, pollution potential and are directly related to the aging of the asphalt. In this work, a voltammetric method was developed seeking to determine sulfur compounds in its reduced form (-II) and oxidized (+II, +IV) in virgin and aged CAP samples, using a mercury electrode in HMDE mode in a non-aqueous medium. To do so, sixteen sulfur compounds were studied in different oxidation states (-II, +II, +IV), obtaining the linear range and detection limit for each compound. The direct application of the method in the CAP samples is impossible due to the highly complex chemistry that the matrix presents, possibly making the determination of compounds not viable. Therefore, the CAP samples were fractionated into functional groups (saturated/aromatic, aliphatic sulfides and thiophenes) by the method adapted from Payzant (1989), employing redox reactions and chromatographic separation by adsorption on silica. After such fractionation, the samples were subjected to a cleaning procedure using solid phase extraction (SPE).